Procedures protocols and options for biological control of weeds in tropical countries - Julien, M.H. (CSIRO. Div. of Entomology, Private Bag no.3, Indooroopilly 4068 (Australia)) (Malaysian Plant Protection Society, 2013)
The concepts underlying biological control are briefly considered and biological control defined so that established procedures and protocols can be better understood. The protocols pertaining to classical biological control of weeds are discussed with the aim of allaying commonly expressed fears concerning introductions of exotic agents. Also exmined are the rising interest in biological control of weeds in the Southeast Asia region, as well as the selection of targets weeds and of agents and options available to develop weed control programmes. It is urged that the Southeast Asia region could increase its capacity for more effective biological control of weeds by developing regional quarantine and training centres